Profile of Anemia on Lung Tuberculosis at Dr. Hasan Sadikin General Hospital and Community Lung Health Center Bandung - Marizka Adzani; Nadjwa Zamalek Dalimoenthe; Indra Wijaya (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis that can cause anemia. Anemia is a lack of erythrocyte mass needed to carry adequate oxygen to the whole bodies. The aim of this study was to describe the anemia in adult lung TB patients at Dr. Hasan Sadikin General Hospital and Community Lung Health Center (Balai Kesehatan Paru Masyarakat, BKPM) Bandung.Methods: This descriptive study was conducted from August to October 2014. Study subjects were adult TB patients who came for their first control to TB Clinic Dr. Hasan Sadikin General Hospital and BKPM Bandung after receiving oral antituberculosis drugs, and willing to comply in study. The exclusion criteria were patients with other chronic diseases, pregnant, menorrhagia, and hemoptoe. Three mL of vein blood was taken and put into EDTA tube for routine hematologic measurement using automatic hematologic analyzer, sysmex KX-21®.Results: There was 31 (63.26%) from 49 adult lung TB patients suffered anemia. In male subjects, mild and moderate anemia were found 57.14% and 42.86% respectively, and in female subjects were 58.82% and 41.18% respectively. In males, there were 42.86% normochromic normocytic, 42.86% hypochromic microcytic, 7.14% normochromic microcytic, and 7.14% hypochromic normocytic, while in females, there were 5.88% normochromic normocytic, 47.06% hypochromic microcytic, 17.65% normochromic microcytic, 29.41% hypochromic normocytic.Conclusions: Anemia is found in 63.26% adult lung TB patients, most of which are mild anemia and hypochromic microcytic, especially in female subjects. [AMJ.2016;3(1):137–40] DOI: 10.15850/amj.v3n1.473